PENGARUH SELF-COMPASSION TERHADAP ACADEMIC BURNOUT PADA MAHASISWA DALAM MENGERJAKAN TUGAS AKHIR - Haura Samma Hasna Althaf; Wanodya Kusumastuti; Widyaning Hapsari (PT. Hasba Edukasi Mandiri, 2026)
Provides a detailed summary of the research This study aims to determine the effect of self-compassion on academic burnout in students working on their final assignments (thesis). The thesis writing process often triggers significant academic pressure that impacts physical and emotional exhaustion, and loss of motivation. In this context, self-compassion is considered a crucial internal coping mechanism to mitigate the risk of burnout. The research method used is quantitative with simple linear regression analysis techniques. The research subjects were 183 students at Muhammadiyah University of Purworejo selected using the Stratified Quota Sampling technique. The data collection instrument in this study used a self-compassion scale and an academic burnout scale. Data analysis also included classical assumption tests such as normality, multicollinearity, and heteroscedasticity tests. The results of the study indicate a highly significant negative influence between self-compassion on academic burnout. Quantitative findings indicate that the self-compassion variable contributes 94.7% to the variation in student burnout levels, while the remaining 5.3% is influenced by other factors outside the study. This proves that the higher students' ability to apply self-compassion, the lower their perceived level of academic burnout. The conclusion of this study confirms that self-compassion serves as an effective psychological buffer for final-year students. By adopting a non-judgmental attitude (self-kindness), recognizing difficulties as a common part of the learning process (common humanity), and maintaining mindfulness, students can be more adaptive in managing stress during thesis writing.